Penatalaksanaan Fisioterapi Pada Kondisi Penyakit Paru Obstruktif Kronis Di Rs Paru Ario Wirawan Salatiga - Saputro, Sigit, Isnaini Herawati, S.Fis, S.Pd, M.Sc (2015)
Background: Chronic obstructive pulmonary disease is a respiratory disorder largely caused by smoking and is characterized by progressive, partially reversible airway obstructive and lung hyperinflation, systemic manifestations, and increasing frequency and severity of exacerbations. Purpose: to know the physiotherapy management in COPD about dyspenia, decreased thorax expansion, expectoration of secret, and breathing muscles of spasm use Infra red, ACBT, and Chest PT. Result: after 6th therapy, the result is decreasing tight of breath T1:5 (severe) T6:5 (severe), still happen spasm at muscles of breathing. Flatting expectoration of secret. Flatting axilla thorax expansion T1:2cm to T6:2cm, intercostalis space 4 T1:2cm to T6: 2cm, in processus xyphoideus T1:3cm to T6:3cm. Conclusion: Infra red, ACBT dan Chest PT can reduce dispenia ,increase power of breathing muscles, increase thorax expansion and increase kick out mucus from lung.